(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Resume; This article is devoted to current problems of dermatovenerology and cosmetology. In the scientific study, the results of the clinical study of the microflora of the skin in vulgar sorghum and the materials obtained as a result of the study of the sensitivity of the isolated microflora to antibacterial drugs are presented. Research results prove that microorganisms belonging to the family of Propionibacterium acnes and Staphylococcus occupy the main place in acne pathogenesis. The study of sensitivity to antibiotics makes it possible to use rational and scientifically based antibiotic therapy.